Consumer behaviour in wine tourism: involvement, destination emotions and place attachment in the wine tourist behaviour during the Porto wine cellars visits context - Santos, Vasco Ribeiro dos (2018)
Tese apresentada à Universidade Fernando Pessoa como parte dos requisitos para obtenção do grau de Doutor em Ciências Empresariais